Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\Leftrightarrow\left(x+1+x-1\right)\left(x+1-x+1\right)-3\left(x^2-1\right)=4\)
\(\Leftrightarrow2x.2-3x^2+3=4\)
\(\Leftrightarrow-3x^2-4x-1=0\)
\(\Leftrightarrow-3x^2-3x-x-1=0\)
\(\Leftrightarrow-3x\left(x+1\right)-\left(x+1\right)=0\)
\(\Leftrightarrow\left(x+1\right)\left(-3x-1\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x=-1\\x=-\frac{1}{3}\end{cases}}\)
- Ta có: \(\frac{x+4}{x-2}=\frac{-3}{4}\)
\(\Rightarrow4.\left(x+4\right)=-3.\left(x-2\right)\)
\(\Leftrightarrow4x+16=-3x+6\)
\(\Leftrightarrow4x+3x=6-16\)
\(\Leftrightarrow7x=-10\)
\(\Leftrightarrow x=-\frac{10}{7}\)
Vậy \(S=\left\{-\frac{10}{7}\right\}\)
a)
(x+4)(3x-5) = 0
=> x + 4 = 0 hoặc 3x-5 = 0
x = -4 x = 5/3
b)
2x2 + 7x + 3 = 0
2x2 + 6x + x + 3= 0
(2x+1)(x+3) = 0
=> 2x+1 = 0 hoặc x + 3 = 0
x = -1/2 x = -3
1. -4x( x + 3 )( x - 4 ) - 3x( x2 - x + 1 )
= -4x( x2 - x - 12 ) - 3x( x2 - x + 1 )
= -4x3 + 4x2 + 48x - 3x3 + 3x2 - 3x
= -7x3 + 7x2 + 45x
2. a) 4x( x - 5 ) - ( x - 1 )( 4x - 3 ) = 5
<=> 4x2 - 20x - ( 4x2 - 7x + 3 ) = 5
<=> 4x2 - 20x - 4x2 + 7x - 3 = 5
<=> -13x - 3 = 5
<=> -13x = 8
<=> x = -8/13
b) 6( x - 3 )( x - 4 ) - 6x( x - 2 ) = 4
<=> 6( x2 - 7x + 12 ) - 6x2 + 12x = 4
<=> 6x2 - 42x + 72 - 6x2 + 12x = 4
<=> -30x + 72 = 4
<=> -30x = -68
<=> x = 34/15
Bài 1 :
\(-4x\left(x+3\right)\left(x-4\right)-3x\left(x^2-x+1\right)\)
\(=-7x^3+7x^2+45x\)
Bài 2 :
a, \(4x\left(x-5\right)-\left(x-1\right)\left(4x-3\right)=5\)
\(\Leftrightarrow4x^2-20x-\left[4x^2-7x+3\right]=5\)
\(\Leftrightarrow4x^2-20x-4x^2+7x-3=5\)
\(\Leftrightarrow-13x-8=0\Leftrightarrow x=-\frac{8}{13}\)
b, \(6\left(x-3\right)\left(x-4\right)-6x\left(x-2\right)=4\)
\(\Leftrightarrow6x^2-42x+72-6x^2+12x=4\)
\(\Leftrightarrow-30x+68=0\Leftrightarrow x=\frac{34}{15}\)
Answer:
\(\left(x-5\right)^2+\left(x+4\right)\left(3-x\right)=4\)
\(\Rightarrow x^2-10x+25+3x-x^2+12-4x-4=0\)
\(\Rightarrow-11x+33=0\)
\(\Rightarrow x=3\)